County Statistics File 4 (CO-STAT 4): (United States) ([Verlag nicht ermittelbar], 1992)
This compilation of data, which was gathered from a variety of federal agencies and private organizations, provides information for the United States as a whole, the 50 states and the District of Columbia, and 3,141 counties and county equivalents (defined as of April 24, 1989). Data are included for the following general areas: age, ancestry, agriculture, banking, business, construction, crime, education, elections, government, health, households, housing, labor, land area, manufactures, money income, personal income, population, poverty, retail trade, service industries, social insurance and human services, veterans, vital statistics, wholesale trade, and journey to work.